ESTABLISHING NORMAL REFERENCE RANGES FOR WHITE BLOOD CELL AND PLATELET COUNTS IN ADULT MALES: A REGIONAL STUDY IN MUZAFFARABAD DISTRICT. : JPUMHS;2024:14:04,4-14. http://doi.org/10.46536/jpumhs/2024/14.04.555 - Jamil Ahmed Kayani1, Ayesha Siddiq2, Manzoor Ali Khan3, Maida Khalid4, Shamal Iqbal5, Sumira Abbas6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Many studies have established normal reference values for hematological indices in various populations, but these values can be influenced by factors like sex, age, ethnicity, and socio-environmental conditions. It is crucial to develop specific reference values for each population. For the Pakistani population, existing hematological reference values are based on Western populations and may not be suitable. OBJECTIVE: To determine normal reference values for white blood cells and platelets for adult male population in district Muzaffarabad. METHODOLOGY: This cross-sectional study took place in District Muzaffarabad from July 2022 to February 2023, involving 384 healthy adult men, selected through stratified disproportionate random sampling. Data was collected through a structured questionnaire. The collected blood samples were analyzed using the Sysmex Hematology Analyzer KX21, Japan. Reference values for Total Leukocyte and platelets count were established and compared with existing reference values. RESULTS: The mean age of 29.11 years, about 71.87% n=276 were from rural areas, 44.27% n=170 belonged to the lower socioeconomic class, 66.67% n=256 had completed high school education. The mean Total Leukocyte count TLC was 7,579/µl, with a range of 4,280 to 10,380/µl, while the mean platelet count PLT# was 284,271/µl, ranging from 195,891 to 365,678/µl. The independent t-test revealed no statistically significant differences in the mean Leukocytes and Platelets across different age groups, areas of residence, education levels, and socioeconomic statuses p>0.05. CONCLUSION: Normal reference values for TLC and Platelets for adult male population in district Muzaffarabad are different from the reference values which are currently used.